Healthy Lifestyle of Prophet Muhammad in Science Perspective - Fakhruddin, Agus; Sukmafitri, Ajeng (International Journal of Psychosocial Rehabilitation, 2020)
Health is an essential thing in the life of every living thing. A healthy life can improve one’s performance in activities. However, today many people have dangerous diseases due to unhealthy behavior. In fact, in prophetic times, the Prophet Muhammad, as a role model dor Muslims never experienced pain during his life. This study examines the habits of the Prophet Muhammad viewed by science as a healthy lifestyle that needs to be implemented in everyday life. The research method used is qualitative research through literature review. In this study, some literature related to the Prophet Muhammad’s habits were reviewed and analyzed to obtain a collection of information. Some of the Prophet Muhammad’s habits obtained from the results of studies were then linked to science from various works of literature. The results showed that the Prophet Muhammad’s various habits have good potential for health in terms of religion and science. This study’s results in the form of a lifestyle can be implemented in daily life and become a reference for the community to create a healthy life.